الألفاظ المَعبِّرة عن المطر في القرآن الكریم دراسة دلالیة - أ.د. حسین محیسن ختلان البكري (College of Education for Women, 2019)
The Holy Koran is the highest text in the eloquence, It is one of the important sources of the linguistic syntactic and eloquent study; it impacts upon these sciences Avery intense impact through advancing its verses as an argument in the confirmation of the significance of the term The holy Koran was and still the fountain of the linguistic studies, as they tend towards it since the second century of the hegira. So this research is a study of the expressive terms concerning the rain in the holly Koran, a linguistic study; it aims to study the term concerning its linguistic and conjugate significance and its expression concerning the rain through reality and metaphor.